2019
DOI: 10.1080/09168451.2018.1528139
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics of Japanese Black cattle beef and other meats using gas chromatography–mass spectrometry

Abstract: Progress in metabolomic analysis now allows the evaluation of food quality. This study aims to identify the metabolites in meat from livestock using a metabolomic approach. Using gas chromatography–mass spectrometry (GC/MS), many metabolites were reproducibly detected in meats, and distinct differences between livestock species (cattle, pigs, and chickens) were indicated. A comparison of metabolites between tissues types (muscle, intramuscular fat, and intermuscular fat) in marbled beef of Japanese Black cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 30 publications
2
42
0
1
Order By: Relevance
“…The abundance of amino acids, amino compounds, and nucleic-acid metabolites clearly reflects the lean meat content of Holstein beef. Previous studies also showed the relationship between metabolomic profiling and beef quality [7][8][9][10][11]. These results indicate that metabolomic analysis is an optimum approach to identify quality-related chemical components of beef.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The abundance of amino acids, amino compounds, and nucleic-acid metabolites clearly reflects the lean meat content of Holstein beef. Previous studies also showed the relationship between metabolomic profiling and beef quality [7][8][9][10][11]. These results indicate that metabolomic analysis is an optimum approach to identify quality-related chemical components of beef.…”
Section: Discussionmentioning
confidence: 53%
“…The meat aging period in the present study was at 4 • C for 7 days after slaughter. In contrast, the aging in Ueda et al was at 4 • C for 20 days [9]. On the other hand, results showing a higher amount of maltose in Wagyu beef than in Holstein beef were common to both experiments.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations